2023
DOI: 10.1186/s12890-023-02327-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of three sputum specimens for the diagnosis of Mycobacterium avium complex pulmonary disease

Abstract: Background In Mycobacterium avium complex pulmonary disease (MAC-PD), diagnosis requires a positive culture from at least two separate expectorated sputum specimens. The optimal number of sputum examinations remains unclear. Objective This study sought to elucidate the diagnostic yield of acid-fast bacilli in MAC-PD using 3 sputum specimens and to clarify the clinical characteristics of patients with MAC-PD diagnosed using 3 sputum specimens. Furth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Urabe et al reported the usefulness of three sputum specimens in 139 patients with the diagnosis of MAC-LD [ 14 ]. They used OC only and reported that only 16.5% (23/139 patients) of patients were diagnosed by three sputum examinations and 81.3% (113/139) required bronchoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Urabe et al reported the usefulness of three sputum specimens in 139 patients with the diagnosis of MAC-LD [ 14 ]. They used OC only and reported that only 16.5% (23/139 patients) of patients were diagnosed by three sputum examinations and 81.3% (113/139) required bronchoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…As per the latest American Thoracic Society (ATS)/ European Respiratory Society (ERS)/ European Society of Clinical Microbiology and Infectious Diseases (ESCMID)/ Infectious Diseases Society of America (IDSA) clinical practice guideline on the treatment of nontuberculous mycobacterial pulmonary disease ( 4 ), the diagnosis of MAC pulmonary disease requires at least two positive sputum cultures (or one positive sample from a lavage or biopsy). Even for the most prolific sputum producer, this process may take several weeks, but many people struggle to produce samples at all ( 5 , 6 ). For these patients, it is normally recommended that they proceed to bronchoscopy (or biopsy), but this can be an unpleasant and invasive procedure, and not all patients are suitable.…”
mentioning
confidence: 99%